THE ROLE OF BOJONEGORO REGENCY GOVERNMENT IN IMPLEMENTING SOCIOECONOMIC ENGINEERING POLICY TO ENHANCE THE WELFARE OF RICE FARMERS IN BOJONEGORO REGENCY - Arba’atun, Yuni; Prihartini, Indah; Ariadi, Bambang Yudi; Tain, Anas (Ridwan Institute, 2024)
This study aims to examine the role of the Bojonegoro Regency Government in implementing socioeconomic engineering policies to enhance the welfare of rice farmers in the region. The research population consists of all rice farmers participating in the Independent Farmer Program (PPM) and affiliated with 1,672 Farmer Groups spread across 28 sub-districts in the area. This study was conducted by distributing questionnaires to rice farmers who participated in PPM. The questionnaires were subsequently analyzed using the SPSS program. The Sobel test was used to analyze the indirect effects of social economic engineering policies on farmer welfare. The results indicate that the implementation of the Role of Bojongoro regency government in the implementation process of socio-economic engineering policy makes a significant contribution to improving the Welfare of Rice Farmers, particularly in terms of providing capital assistance and agricultural purchase guarantees. The findings of this study are supported by empirical data and analyzed statistically, thus providing evidence of the significant role of local government in promoting inclusive and sustainable rural development in the regions, which can directly or indirectly impact the improvement of rice farmer welfare in the areas.